RAB39B as a Chemosensitivity-Related Biomarker for Diffuse Large B-Cell Lymphoma - Xu, Cong; Liang, Ting; Liu, Jing; Fu, Yunfeng (Frontiers in Pharmacology, 2022)
Background Diffuse large B-cell lymphoma (DLBCL) is the most common aggressive lymphoma with increased tendency to relapse or refractoriness. RAB39B, a member of the Ras-oncogene superfamily, is associated with a variety of tumors. Nevertheless, the role of RAB39B in DLBCL is still unknown. This study aimed to identify the role of RAB39B in DLBCL using integrated bioinformatics analysis. Methods RAB39B expression data was examined using TIMER, UCSC and GEO database. The LinkedOmics database was used to study the genes and signaling pathways related to RAB39B expression. Protein-protein interaction network was performed in STRING. TIMER was used to analyze the correlation between RAB39B and infiltrating immune cells. The correlation between RAB39B and m6A-related genes in DLBCL was analyzed using TCGA data. RAB39B ceRNA network was constructed based on starBase and miRNet2.0 database. Drug sensitivity information was obtained from GSCA database. Results RAB39B was highly expressed in multiple tumors including DLBCL. Protein-protein interaction network showed enrichment of autophagy and RAS family proteins. Functional enrichment analysis of RAB39B co-expression genes revealed that RAB39B was closely related to DNA replication, protein synthesis, cytokine-cytokine receptor interaction, JAK-STAT signaling pathway, NF-kappa B signaling pathway and autophagy. Immune infiltrate analysis showed that the amount of RAB39B was negatively correlated with iDC, Tem and CD8 T cell infiltration. CD4+ T cell and DC were negatively correlated with CNV of RAB39B. DLBCL cohort analysis found that RAB39B expression was related to 14 m6A modifier genes, including YTHDC1, YTHDC2, YTHDF1, YTHDF2, YTHDF3, RBMX, ZC3H13, METTL14, METTL3, RBM15, RBM15B, VIRMA, FTO and ALKBH5. We constructed 14 possible ceRNA network of RAB39B in DLBCL. RAB39B expression was associated with decreased sensitivity of chemotherapy drugs such as dexamethasone, doxorubicin, etoposide, vincristine, cytarabine and poor overall survival in DLBCL. In vitro experiments showed that RAB39B was associated with the proliferation, apoptosis and drug-sensitivity of DLBCL cells. Conclusions RAB39B is abnormally elevated and related to drug resistance and poor OS in DLBCL, which may be due to its involvement in immune infiltration, m6A modification and regulation by multiple non-coding RNAs. RAB39B may be used as an effective biomarker for the diagnosis and treatment of DLBCL.